Valutare il cambiamento di competenze e atteggiamento professionale a seguito del corso di formazione iniziale per insegnanti di sostegno - Gaetano Domenici; Valeria Biasi; Federica Wolf; Conny De Vincenzo (LED Edizioni Universitarie, 2022)
Attitudes and expectations are key factors to consider in teacher training in general and specialist support teachers in particular. The research conducted at the Unicamillus University of Rome, of which some of the procedural results achieved are presented here, highlights the importance of the role that the levels of perceived self-efficacy play in promoting the learning of trainee teachers. This contribution illustrates, in particular, the procedure and the results of a survey conducted on the participants of a specialization course for support with the aim of detecting the attitudes and expectations of teachers  before and after the training experience. In this regard, at the beginning and at the end of the course, teachers were given online questionnaires prepared ad hoc for the collection of socio-demographic information and their opinions on the training course; on both occasions, the teachers responded to the Teacher Self-Effectiveness Scale to assess the impact of the training received. The contribution that specific teaching and organizational methods - such as lessons, workshops, internships - have made in ensuring the qualification of the training course was also analyzed. The results showed a significant increase in the perception of self-efficacy at the end of the training, in particular in self-efficacy in involving students, in self-efficacy in teaching strategies and in self-efficacy in classroom management. Furthermore, the teachers were satisfied with the training received and considered the activities proposed during the course to be useful. Investigations of this type can contribute to a better characterization of training courses for support.